Antenatal Steroid Therapy for Fetal Lung Maturation and the Subsequent Risk of Childhood Asthma: A Longitudinal Analysis. (16th May 2010) - Pole, Jason D.; Mustard, Cameron A.; To, Teresa; Beyene, Joseph; Allen, Alexander C.
Abstract : This study was designed to test the hypothesis that fetal exposure to corticosteroids in the antenatal period is an independent risk factor for the development of asthma in early childhood with little or no effect in later childhood. A population-based cohort study of all pregnant women who resided in Nova Scotia, Canada, and gave birth to a singleton fetus between 1989 and 1998 was undertaken. After a priori specified exclusions, 80, 448 infants were available for analysis. Using linked health care utilization records, incident asthma cases developed after 36 months of age were identified. Extended Cox proportional hazards models were used to estimate hazard ratios while controlling for confounders. Exposure to corticosteroids during pregnancy was associated with a risk of asthma in childhood between 3–5 years of age: adjusted hazard ratio of 1.19 (95% confidence interval: 1.03, 1.39), with no association noted after 5 years of age: adjusted hazard ratio for 5–7 years was 1.06 (95% confidence interval: 0.86, 1.30) and for 8 or greater years was 0.74 (95% confidence interval: 0.54, 1.03). Antenatal steroid therapy appears to be an independent risk factor for the development of asthma between 3 and 5 years of age.